Flavonoid–alkylphospholipid conjugates elicit dual inhibition of cancer cell growth and lipid accumulation. Issue 61 (4th July 2019) - Zhou, Zhengwei; Luo, Biyao; Liu, Xi; Chen, Mimi; Lan, Wenjun; Iovanna, Juan L.; Peng, Ling; Xia, Yi
Abstract : Quercetin–alkylphospholipid conjugates are promising chemical entities with anticancer activity and the ability to inhibit lipid synthesis and metabolism. Abstract : Cancer development is often associated with lipid metabolic reprogramming, including aberrant lipid accumulation. We create novel paradigms endowed with dual functions of anticancer activity and inhibition of lipid accumulation by conjugating the natural product quercetin and synthetic alkylphospholipid drugs, and harnessing the biomedical effects of both. These conjugates offer fresh perspectives in the search for anticancer candidates.